PENGUATAN GENERASI MODERAT SISWA SMAN SUTOJAYAN DAN SMAN 4 KOTA BLITAR - Nanang Zamroji; Umi Nahdiyah; Adi Tri Atmaja; Fathul Niam; Awaludin Jamil; Ana Safitri; Chairumin Alfin; Redhitya wempi Ansori; Agus Yulianto; Zainal Rosyadi; Siti Uswatun Kasanah; Khoirul Wafa (Jurnal Padamu Negeri, 2025)
Indonesia is a country characterized by a diversity of religions and beliefs. All elements of society are needed to achieve a harmonious life. Intolerant and extreme behavior not only targets the general public in the real and virtual worlds, but has now spread to educational institutions. Activities such as halaqah (Islamic religious gatherings) and other closed religious studies that are not accompanied by a moderate understanding of religious teachers can encourage the emergence of exclusivist, exploitative, and intolerant attitudes in educational institutions. Strengthening moderate attitudes must be carried out in a structured manner in various aspects of community life, including educational institutions, because they play a strategic role in fostering moderate understanding and can even serve as laboratories for religious moderation. If the strengthening of moderate attitudes in educational institutions is not optimized, they will certainly become easy targets for the infiltration of splinter and intolerant ideologies. Therefore, educational institutions are a highly effective medium for strengthening the character of students who are broad-minded, open, and tolerant in the dynamics of life as a diverse nation and state.